Do Albumin Losses To Dialysate Affect Serum Albumin Levels in Maintenance Hemodialysis Patients? - Tomohito Matsunaga (The Korean Society of Nephrology, 2012)
Serum albumin (s-Alb) is not reliable marker of nutritional status in maintenance hemodialysis (MHD) patients, because s-Alb levels are not only affected by nutritional intake but also other factors including inflammation, age, comorbidity and albumin loss to dialysate. In this study we evaluated the influence of albumin losses to dialysate on s-Alb levels. The sixty-four patients who have received MHD were analyzed (39 males, 45 females; diabetes 14; mean age 65.5±10.9 years; duration of HD treatment 13.2±6.8 years). All patients received four-hour HD session three times per week with ultra-pure dialysate. Pre-dialysis levels of s-Alb were measured at the first HD session in the week. Based on two-day dietary records and photographs, the accomplished dietitians calculated dietary energy intake (DEI) and dietary protein intake (DPI). LBM, fat mass and ECF/TBW (as an index of fluid overload) were measured using BIA (Inbody 3.0) after the first post-dialysis. Albumin losses to dialysate were measured by collecting total amount of dialysate during one dialysis session. The mean levels of s-Alb and albumin losses to dialysate were 3.46±0.26 g/dl (2.8-4.1) and 0.87±1.03 g/session (0.00-4.84). The s-Alb levels were not correlated with albumin losses, but correlated with CRP, sex, age, DEI/post-BW and LBM. The multiple regression analysis with s-Alb levels showed CRP and sex were independent variables, but not DEI/post-BW, nPCR, Kt/Vurea, LBM, fat mass, ECF/TBW and Albumin losses (r=0.61, p<0.01). In conclusion, pre-dialysis s-Alb levels were affected by, not albumin losses to dialysate, but sex and CRP reflecting the inflammatory status.